Floristic Feature of Plant Cover Associated with Some Species of Genus Suaeda in Egypt - El-Amier, Yasser A; El-Halawany, El-Sayed F; Khudhair, Ahmed K (International Journal of Natural Sciences Research, 2017)
The present study provides an investigation of the floristic features, including list of plant species, life-span, life-form spectra and floristic analysis of the plant life associated with Suaeda maritima, Suaeda monoica, Suaeda pruinosa and Suaeda vera in family Chenopodiaceae in the Deltaic Mediterranean coast and Wadi Hagul of Egypt. This study also aims at recording the floristic structure to be used in measurement of plant diversity and ecological conservation plan of the study area in future. The total number of the recorded plant species surveyed in the study area was 103 species belonging to 80 genera and related to 23 families. These species are classified into three major groups according to their duration (life-span) as follows: 47 annuals (45.63%), 2 biennial (1.94%) and 54 perennials (52.42%). The main families are: Asteraceae (23 species), Poaceae (19 species) followed by Chenopodiaceae (17 species) and Fabaceae (7 species). The recorded species are also grouped under six types of life forms as follows: therophytes, chamaephytes, cryptophytes (comprising geophytes and helophytes), hemicryptophytes, phanerophytes and parasites. Out of the recorded species 56 species (about 54.36 % of the total species) are Mediterranean taxa, 18 species (17.48%) was belonging to Monoregional Saharo-Sindian element, 19 species are either Cosmopolitan (10 species = 9.71%), Palaeopical (5 species = 4.85%), Neotropical and Pantropical (2 species = 1.94 each).